Arduino Based Turkey Egg Incubator With Molen Rotation Method - Ardi Prayugo; Syamsudduha Syahrorini (Universitas Muhammadiyah Sidoarjo, 2021)
Today's modern world of hatching many turkey eggs uses various incubators. Arduino-based turkey egg incubator with the molen rotation method uses an Arduino microcontroller that is connected to a DHT11 sensor for turkey egg incubator using the molen rotation method. Temperature and humidity are the main factors to determine the success at hatching of eggs, but also the need for the fertilization process in the eggs to be hatched because fertilization also determines the success rate at hatching eggs. Testing of the incubator is carried out directly from the turkey egg incubator at the temperature in the room and rotates it with the automatic spinning method with an angle of 360 ° every 4 hours. DHT11 can detect temperature and humidity in the incubator room, the optimal temperature for hatching turkey eggs is 37 ° -38 ° C and the optimal humidity is 55-60% RH, and the servo motor is able to move to move the egg rack according to the time specified. The measurement results of the DHT11 sensor readings are as desired with a minimum temperature reading of 37⁰C and a maximum temperature of 39⁰C with humidity that has been set at 55-60% and the molen rotation method runs according to the desired time every 6 hours for 4 times with 360 ⁰ rotation, at days 1-26 turkey eggs hatch with a result of 3: 2 in the sense that 3 successfully hatched and 2 failed to hatch.